Internet and Face-to-face Cognitive Behavioral Therapy for Postnatal Depression Compared With Treatment as Usual: Randomized Controlled Trial of MumMoodBooster - Jeannette Milgrom; Brian G Danaher; John R Seeley; Christopher J Holt; Charlene Holt; Jennifer Ericksen; Milagra S Tyler; Jeff M Gau; Alan W Gemmill (JMIR Publications, 2021)
BackgroundPrevious research has confirmed that symptoms of postnatal depression (PND) can be ameliorated through internet-delivered psychological interventions. Advantages of internet-delivered treatment include anonymity, convenience, and catering to women who are unable to access face-to-face (FTF) treatments. To date, no research has examined the efficacy of such interventions compared directly with FTF treatments in women clinically diagnosed with PND. ObjectiveThis study aims to compare the efficacy of one of the first web-based cognitive behavioral therapy (CBT) interventions (internet CBT+coach calls) for PND (MumMoodBooster [MMB]) with FTF-CBT in a randomized controlled trial (RCT). MethodsIn this study, 116 postnatal women with a Diagnostic and Statistical Manual for Mental Disorders, Fourth Edition (DSM-IV) diagnosis of major or minor depression were randomized to MMB (39/116, 33.6%), FTF-CBT (39/116, 33.6%), or a treatment-as-usual (TAU) control condition (38/116, 32.8%). Diagnostic status was determined at baseline and at 21-week follow-up using the Structured Clinical Interview for the DSM-IV. Severity of anxiety and depressive symptoms was evaluated using the Depression Anxiety Stress Scales and the revised Beck Depression Inventory at baseline, 12-week follow-up (after treatment), and 21-week follow-up. ResultsOf the 116 participants, 107 (92.2%) had a diagnosis of major depression at baseline. Rates of remission from a major or minor depressive episode at 21 weeks in both the FTF-CBT and MMB groups were superior to that of the TAU group (56.6% and 47.7% less likely to be depressed, respectively) and they were not significantly different from each other. Although remission rates differed between TAU and FTF-CBT, growth models showed that, in terms of symptom reduction across time, the FTF-CBT treatment was not significantly better than TAU. By comparison, MMB was statistically superior to both TAU and FTF-CBT in reducing symptoms of depression, anxiety, and stress from baseline to the 21-week follow-up (large and moderate effect sizes). Thus, after 21 weeks, the average symptom scores for depression and anxiety of women receiving MMB were approximately half those of women in both the TAU and FTF-CBT groups. ConclusionsIn this RCT, MMB was at least as effective as FTF-CBT in achieving remission from a diagnosed PND episode. MMB was superior to TAU and FTF-CBT in encouraging and maintaining reduction of symptom severity over the 21-week follow-up for depressed postnatal women. These findings replicate results of prior studies on MMB that showed clinically significant improvements in depressive symptoms, and they provide direct empirical support that internet-delivered treatment for depressed postnatal women is a viable alternative to FTF treatment. The generalizability of the results needs to be examined in future research, as RCTs of internet-based versus FTF treatments necessarily involve a subset of people who are willing to undertake either modality of treatment. Trial RegistrationAustralia and New Zealand Clinical Trials Registry (ANZCTR) ACTRN12613000881730; https://anzctr.org.au/Trial/Registration/TrialReview.aspx?id=364683&isReview=true